2008
DOI: 10.3310/hta12230
|View full text |Cite
|
Sign up to set email alerts
|

A prospective randomised comparison of minor surgery in primary and secondary care. The MiSTIC trial

Abstract: Non-UK purchasers will have to pay a small fee for post and packing. For European countries the cost is £2 per monograph and for the rest of the world £3 per monograph.You can order HTA monographs from our Despatch Agents:-fax (with credit card or official purchase order) -post (with credit card or official purchase order or cheque) -phone during office hours (credit card only).Additionally the HTA website allows you either to pay securely by credit card or to print out your order and then post or fax it. NHS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
1
5

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(47 citation statements)
references
References 18 publications
(8 reference statements)
2
38
1
5
Order By: Relevance
“…1 The GP surgeons in the current study appear to achieve higher standards of diagnosis, excision completeness, and use of histology than for those reported in that study. However, the range of conditions being operated on seems to be more extensive, and the numbers of pigmented lesions excised, which is at odds with national guidance.…”
Section: Comparison With Existing Literaturecontrasting
confidence: 49%
See 1 more Smart Citation
“…1 The GP surgeons in the current study appear to achieve higher standards of diagnosis, excision completeness, and use of histology than for those reported in that study. However, the range of conditions being operated on seems to be more extensive, and the numbers of pigmented lesions excised, which is at odds with national guidance.…”
Section: Comparison With Existing Literaturecontrasting
confidence: 49%
“…A major trial suggested that the quality of minor surgery carried out in general practice is not as high as that carried out in hospital, although the difference was not great. 1 The investigators of that trial felt there were deficiencies in GPs' recognition of malignant lesions, and possibly in completeness of excision compared with hospital doctors. They stated:…”
Section: Introductionmentioning
confidence: 99%
“…The findings of poorer recognition of skin malignancy by GPs and poorer quality of skin cancer surgery in primary care compared with secondary care have been reported in other UK studies. 8,[13][14][15] Additional concerns around primary care skin cancer treatment stem from fewer primary care MM excision patients receiving specialist management, and GPs reportedly making less use of pathology services than secondary care doctors when conducting minor surgery. 14,15 Internationally, similar trends are reported, although differences between healthcare models, dermatology, and skin surgery training influence outcomes and make translation of findings to the UK less valid.…”
Section: Discussionmentioning
confidence: 99%
“…However, in the current absence of significant investment in primary care dermatological diagnostic skills and skin surgery training, and with UK health policy seeking to reduce delays to definitive cancer treatment, guidelines for primary care triage and referral of suspicious lesions for secondary care management appear to offer patients the best quality, and may be more cost-effective. 4,14 Given the rising incidence of skin cancer, it is not clear whether this approach is sustainable. Policymakers may wish to consider this area of service provision, particularly the proportion of low-risk BCC currently managed in Scottish secondary care, which may be more suitable for treatment closer to the patient's home.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Standards are usually not monitored except by audit of individual doctors, with training generally being informal 'peer to peer' learning, with occasional continuing medical education activities. 2,3 and other countries [4][5][6][7] have shown that skin specialists diagnose and excise skin cancers better than GPs. GPs may unnecessarily remove benign lesions or, because of cost barriers for some patients, refer minor lesions to hospital clinics, placing a high demand on these services.…”
Section: Background and Assessment Of Problemmentioning
confidence: 99%